Digital Tourism Marketing and Local Wisdom : Strategies for Destination Development in Kutai Kartanegara Regency - Dida Rahmadanik; V Rudy Handoko; Rachmawati Novaria; Jaimito Soares Missa (Universitas Teuku Umar, 2026)
Tourism is a strategic sector in supporting sustainable development and economic recovery. Kutai Kartanegara possesses significant potential in natural, cultural, and artificial attractions; however, its contribution to increasing tourist visits has not yet been optimized. The main issue lies in the suboptimal tourism marketing strategies, particularly in the utilization of digital technology and the strengthening of local wisdom as a destination identity. This condition has created a gap between potential and actual tourism development, especially across three strategic zones: the Central Zone, the Highland Zone, and the Coastal Zone. This study aims to analyze Digital Technology-Based and Local Wisdom-Oriented Tourism Marketing Strategies in Kutai Kartanegara Regency. The research employed a qualitative case study design, with data collected through in-depth interviews, observations, and document analysis. The findings indicate that Kutai Kartanegara has substantial potential for developing culture-based digital tourism through policy support and diverse attractions. However, challenges persist in digital infrastructure, technological literacy, and the risk of cultural commodification. Opportunities remain open through the growing trend of experience-based tourism and the region’s strategic position near the new national capital (IKN), which can strengthen destination branding and regional competitiveness.